Learning Management During the COVID-19 Pandemic in Elementary Schools - Maryono; Rejokirono (Journal of Education Reseach and Evaluation, 2024)
Distance learning activities also present problems, such as students and teachers needing adequate device access and a stable internet connection. Based on this, this research aims to analyze the effectiveness of learning management in elementary schools during the COVID-19 pandemic. This type of research is qualitative research. The data collected is primary and secondary. The subjects of this research were all sixth-grade elementary school teachers from 25 state schools and two private schools. The methods used to collect data are interviews, observation, and documentation. The research instruments were interview guidelines, observation guidelines, documentation guidelines, cameras, and notebooks. The technique used to analyze data is qualitative descriptive analysis. The research results show first that during the COVID-19 pandemic, teachers used online, offline, and a combination of online and offline approaches. Second, learning management is in a suitable category. Third, learning obstacles include device availability, network disruption, internet package availability, student discipline, and inadequate teacher information and technology competence. Teachers overcome obstacles by paying attention to the causes of these obstacles. It was concluded that the effectiveness of learning carried out by teachers was adequate so that learning objectives could be achieved optimally.